2014
DOI: 10.9790/0853-13155760
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Lactating Mothers towards Infant oral health care in Udaipur

Abstract: Good oral health is an integral component of good health. Infant oral health (IOH) is the foundation upon which preventive education and dental care must be built to enhance the opportunity for lifetime free of preventable oral diseases. Researches show that mothers play an important role in the decision making processes regarding health care for their children. Identifying the indispensible role of mothers about health care for their children it becomes mandatory to assess the knowledge and attitudes regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In contrast to our study, Suresh et al 13 observed that parents were aware of a healthy diet and dietary practices for their children. In accordance with our study, 11 15 Shetty et al, 11 Abduljalil and Abuaffan, 12 and Peres et al 15 revealed a lack of knowledge among parents regarding the transmission of bacteria on sharing the same utensils and food. In contrast to our study, Nepaul and Mahomed 5 observed that the majority of parents had adequate knowledge about the transmission of bacteria while sharing utensils.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to our study, Suresh et al 13 observed that parents were aware of a healthy diet and dietary practices for their children. In accordance with our study, 11 15 Shetty et al, 11 Abduljalil and Abuaffan, 12 and Peres et al 15 revealed a lack of knowledge among parents regarding the transmission of bacteria on sharing the same utensils and food. In contrast to our study, Nepaul and Mahomed 5 observed that the majority of parents had adequate knowledge about the transmission of bacteria while sharing utensils.…”
Section: Discussionsupporting
confidence: 90%
“…Still, many parents were unaware of the prolonged breastfeeding risk. Similar results were observed in the study by Nepaul and Mahomed, 5 Shetty et al, 11 and Dogra et al, 12 who found that around 47–65% of mothers were unaware of the fact that prolonged breastfeeding leads to dental caries.…”
Section: Discussionsupporting
confidence: 88%
“…[ 19 ] The finding of a high proportion of parents unaware of the risk of prolonged breastfeeding is not unique to our study as similar findings were noted from a study conducted among mothers of 3–6-year-old primary-school children from public primary schools of the city, in Rajnandgaonin, India where 65% of mothers were not aware or did not know that prolonged breastfeeding resulted in tooth decay[ 17 ] and a study among 200 rural mothers from nearby villages and 200 urban mothers from Udaipur city that showed 47% of mothers were unaware that frequent and prolonged breastfeeding was associated with dental caries. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the indispensable role of mothers about health care for their children becomes mandatory to assess the knowledge and attitudes regarding infant oral health and educating them as they are the primary caregivers. [5]…”
Section: Discussionmentioning
confidence: 99%